Chapter Wittgenstein's On Certainty and Relativism - Kusch, Martin (De Gruyter, 2016)
One important strand in the contemporary debate over epistemological relativism focuses on the question whether, and to what extent, Wittgenstein in "On Certainty" (1969) leaned towards this position. This paper is a contribution to this strand. My discussion has four parts. I shall begin by out lining my interpretation of Wittgensteinian certainties. Subsequently I shall briefly introduce some central arguments for and against attributing epistemic relativism to "On Certainty". This will be followed by a sketch of the cluster of ideas that-on my analysis-define important versions of the doctrine in question. And finally I shall give my own interpretation of "On Certainty" in relation to epistemic relativism.